Aligment Feed Water Pump menggunakan Metode Laser PT. Riau Andalan Pulp and Paper Pelalawan, Riau - Dinova, Alfito; Arief, Dodi Sofyan; Dalil, M; Junaidi, Abdul Khair (Proksima, 2024)
Alignment is a process that aligns two shaft axes that are not straight to centric (between the driving shaft and the driving shaft axis). Correct alignment is needed so that checks are completed on the correct clutch, so that offset misalignment and angle misalignment do not occur again which results in damage to machine components which is detrimental to the industry. Misalignment is a condition where there is a deviation at the point between two connected axes (two axes are not located on the same axis). If misalignment occurs in the clutch, it will accelerate damage to the clutch, bearings and other components, and cause excessive vibration. The purpose of writing this report is to find out the basic theory of alignment and find out the alignment method using the laser method.